2007
DOI: 10.1590/s0102-05362007000400017
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de tomate 'Débora' minimamente processado armazenado em dois tipos de embalagens

Abstract: Este trabalho teve como objetivo avaliar a qualidade de tomates cv. Débora minimamente processados acondicionados em dois tipos de embalagens. Os frutos foram lavados e sanificados com hipoclorito de sódio (200 mg L-1). A polpa destes frutos foi cortada em cubos (1 cm³) com posterior enxagüe em solução de hipoclorito de sódio (20 mg L-1), acondicionada em sacos de polipropileno (PP) ou copos de tereftalato de polietileno (PET) e armazenada a 5°C por 8 dias. Durante esse período foram retiradas diariamente amos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
1
1
0
3
Order By: Relevance
“…Oscillations in vitamin C contents similar to what was observed in fruits stored in the PET package were observed by Miguel et al (2007) when studying different packages to store minimally processed tomatoes, but in none of the treatments they observed a reduction similar to that detected in the active type packaging during the storage period.…”
Section: Bioactive Compoundssupporting
confidence: 52%
See 1 more Smart Citation
“…Oscillations in vitamin C contents similar to what was observed in fruits stored in the PET package were observed by Miguel et al (2007) when studying different packages to store minimally processed tomatoes, but in none of the treatments they observed a reduction similar to that detected in the active type packaging during the storage period.…”
Section: Bioactive Compoundssupporting
confidence: 52%
“…Other authors in the study of the shelf life of sweet grape tomatoes and "Coco Cereja" reported a decrease in TA in the materials used (Aguiar et al, 2012). In several other studies, a decrease in TA was observed in some hybrids lower than in others, but there is always a decrease in storage time (BECKLES, 2012;MIGUEL et al, 2007). The decrease in TA occurs in line with the observation of the slight increase in the pH of the fruits over the storage period, which is probably due to the degradation of organic acids, which are used as a substrate for respiratory activity in tissues and which due to the decrease in oxygen inside the package has its metabolism altered.…”
Section: Physical-chemical Characteristicsmentioning
confidence: 75%
“…Micra RS no estádio vermelho de maturação (LISIEWSKA; KMIECIK, 2000) e ratificados por Cheng e Tsang (1998), que afirmam que em tomates frescos as quantidades de nitritos são insignificantes, os valores obtidos nas amostras de tomate de mesa foram bem abaixo dos valores da Ingestão Diária Aceitável (IDA) de acordo com o Joint Expert Committee on Food Additives (FAO/WHO, 2003) , que são de 0 a 222 mg para o nitrato e de 0 a 4,2 mg de nitrito por dia para um adulto de 60 kg de peso corporal. Na análise toxicológica na quantificação de multirresíduos e benzimidazóis, não foram detectados valores superiores aos açúcar e ácido (ZAMBRANO et al, 1996;MIGUEL et al, 2007) e, portanto, boa qualidade (GIL; CONESSA; ARTÉS, 2002). A diferença da relação do SST/ATT nas amostras de tomate cultivado no sistema convencional pode ser influenciada pelas cultivares, estádios de maturação, manejo, fertilização, irrigação e composição do solo (FELTRIN et al, 2002).…”
Section: Resultsunclassified
“…Maiores valores, de 4,09 a 4,38, foram registrados para frutos da cv. Débora (MIGUEL et al, 2007); de 4,16 a 4,20, para tomate da cv. Santa Clara (SAMPAIO; FONTES, 1998); 4,18, para tomate da cv.…”
Section: Resultsunclassified
“…Em estudo desenvolvido por Miguel et al (2007), ao se armazenar em refrigeração (5º C, com variação de 1,03º C) tomate em cubos por 8 dias, observou-se perda da coloração avermelhada, provavelmente associada à perda de licopeno e perda de massa de 21,3% que é atribuída à modificação nas estruturas e na composição da parede celular devido à ação de enzimas (HAMMOND;RENZI, 2013).…”
Section: Resultsunclassified